Treatment of testicular tumors - Lockhart, Jorge L. (Cirugía del Uruguay, 1978)
The author refers to the experience of Duke University in the treatment of 134 testicle tumors. He sets forth general guidelines for treatment according to the tumor's evolutive stage, as per the classification proposed by Mostofi. Stress is laid on the importance of Markers (H.G. C. and A.F.P.) in the patient's evolution, as an index for detecting the tumor's presence. The author concludes that improvement in results obtained in the treatment of these tumors is due to: 1. Aggressive surgical therapy of primary tumor and regional lymph nodes. 2. The considerable value of radiotherapy in seminomas. 3. New chemiotherapeutic programs. 4. N ew radioinmunotests for Markers, which are essential for determining prognosis and response to the treatment employed.